Influence of Spousal Support on the Relationship between Acculturative Stress and Sense of Parenting Competence among Married Vietnamese Immigrant Women - So Hee Kim; Yoon Goo Noh (Korean Society of Women Health Nursing, 2018)
PURPOSE: To identify the effects of spousal support on the relationship between acculturative stress and sense of parenting competence among married Vietnamese immigrant women. METHODS: The sample for this study consisted of 175 married Vietnamese immigrant women in Gyeongsangnam-do. Data were analyzed using descriptive statistics, t-test, ANOVA, Scheffé test, Pearson correlations, and hierarchical multiple regression with SPSS/WIN 23.0. RESULTS: (a) sense of parenting competence was negatively correlated with acculturative stress, whereas a positive correlation was observed with spousal support; (b) spousal support mediated the relationship between acculturative stress and sense of parenting competence. CONCLUSION: Results of the study suggest that spousal support decreases the negative effects of acculturative stress on sense of parenting competence. Therefore, we need to find ways to strengthen spousal support for married Vietnamese immigrant women.